Dissecting the understanding of students about our teaching methods – a single institute, analytical cross-sectional study - Athar, Unsa; Mubashir, Muhammad; Afzal, Muhammad Zeeshan; Usmani, Natasha Taha (Journal of the Pakistan Medical Association, 2023)
Objectives: To measure the perception of medical students regarding different methods of active learning, and its association with the year of study. Method: The analytical cross-sectional study was conducted at Shalamar Medical and Dental College, Lahore, Pakistan, from May to September 2020, and comprised medical students of either gender from first to final year of studies. Data was collected using an online questionnaire regarding different methods of active learning and e-learning. Perceptions and their association with the year of study were worked out. Data was analysed using SPSS 16. Results: Of the 270 subjects, 155(57.4%) were females and 115(42.5%) were males. Overall, 39(14.4%) students were from the first year of studies, 32(11.9%) second, 47(17.4%) third, 120(44.4%) fourth and 32(11.9%) were from the final year of medical studies. Most students preferred class lectures as the teaching method of choice 240(89%), followed by small group discussions 156(58%). Students showed positive perception of different learning methods except e-learning 78(28.89%). The association between perceptions and the year of study was statistically significant (p< 0.05). Conclusion: Students apparently enjoyed using different interactive methods, but were apprehensive about online learning. Key Words: Active learning, Different methods of active learning, E-learning, Medical education, Online learning, Perception of medical students.